Electronic money in russia: current state and problems of development - T. G. Bondarenko; E. A. Isaeva (Статистика и экономика, 2016)
Article is devoted to urgent problems of non-cash methods of calculation development by using electronic money – as one of the modern economically developed state strategic tasks. On modern economic science strong influence appears informatization process. The control expansion tendency, influence and distribution of commerce due to informatization of society led to emergence of the new phenomenon – information economy. Information economy brought new economic events which owing to their novelty are insufficiently studied to life. It is possible to carry electronic money to such phenomena of modern network economy Relevance and, in our opinion, timeliness of this scientific work, consisting in novelty of this non-cash payment method, its prospects and innovation within non-cash methods of calculations. Authors set as the purpose – studying of problems and the prospects of development of electronic money in the Russian Federation. In article theoretical bases of electronic money functioning are described. Determinations and classifications dismissed non-cash a method, and also the principles of electronic money functioning are considered, the questions of their historical development are raised.Authors analyzed statistical data on development of electronic services and channels of their using. Features, benefits and shortcomings of the current state of the market of electronic money are studied. The emphasis on that fact that in modern conditions considerable number of economic actors perform the activities, both in the real environment of economy, and within the virtual environment that promotes expansion of methods of their customer interaction by means of technical devices of personal computers, mobile phones is placed. In article common problems and tendencies of payments with using an electronic money are designated, the research on assessment of the current state and the prospects of electronic money development and services which allowed to confirm analytical calculations of the marketing agencies on this perspective is conducted. The carried-out author’s interviewing allowed to draw conclusions on different degree of popularity about electronic money, most of respondents gives preference to other methods of cashless payment, namely cards and terminals/ATMs. Most of respondents plan to use further electronic money; negative experience has only 2% of respondents. The practical importance of the conducted research consists in identification the future of electronic money in the Russian Federation. The Russian scientists concerning functioning of electronic money, and also the federal law, and data of the official sites of the organizations specializing in subject domain formed a theoretical and information basis of a research. In this article were used and general scientific methods of data collection, methods of a research and a technique of assessment of their reliability and sufficiency found the application: quantitative, comparative, logical analysis and synthesis.